KOMUNIKASI INTERPERSONAL FOTOGRAFER PIONEER WEDDINGS PICTURES DENGAN KLIEN - Yudhistira, Muhammad Asral Dewangga; Suryo S, Herning; Muadz, Muadz (Solidaritas, 2024)
ABSTRACKThis study aims to determine the interpersonal communication that Pioneer Weddings Pictures photographers do with clients to get good photos. This study used descriptive type qualitative methods, researchers also used Miles and Huberman data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. Researchers also used purposive sampling techniques to determine which informants were experts and trustworthy statements to be used to source the data, informants in this study were photographers and clients of Pioneer Weddings Pictures. The results of this study were obtained using interpersonal communication theory with a humanitist approach from Joseph Devito which consists of five aspects, namely, openness, empathy, support, positive attitude, and equality. The interpersonal communication that Pioneer Weddings Pictures photographers have with clients is very good both in and outside the photo shoot. So that photographers and clients can give each other trust and respect so as to minimize debate, good communication is very necessary to get a good photo in accordance with what is desired by both parties. Keywords : Interpersonal Communication, Photographer, Client